2021
DOI: 10.3390/ijms222111504
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Functional Role of RIPK4 in Melanoma

Abstract: The receptor-interacting protein kinase 4 (RIPK4) plays an important role in the development and maintenance of various tissues including skin, but its role in melanoma has not been reported. Using patient-derived cell lines and clinical samples, we show that RIPK4 is expressed in melanomas at different levels. This heterogenous expression, together with very low level of RIPK4 in melanocytes, indicates that the role of this kinase in melanoma is context-dependent. While the analysis of microarray data has rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Several studies indicate that RIPK4 can act as both a tumor suppressor and a tumor oncogene, depending on the type of cancer (Xu et al 2020 ). While it has been reported that RIPK4 is involved in skin tumorigenesis by regulating DLV2 or Pkp1 phosphorylation (Huang et al 2013 ; Lee et al 2017 ), our recent study shows an important role of this kinase in melanoma progression by involvement in NFκB and Wnt/β-catenin transduction signaling leading to increased migration, invasive potential, and cell proliferation as well tumor growth in vivo (Madej et al 2021 ; Wronski et al 2024 ).…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…Several studies indicate that RIPK4 can act as both a tumor suppressor and a tumor oncogene, depending on the type of cancer (Xu et al 2020 ). While it has been reported that RIPK4 is involved in skin tumorigenesis by regulating DLV2 or Pkp1 phosphorylation (Huang et al 2013 ; Lee et al 2017 ), our recent study shows an important role of this kinase in melanoma progression by involvement in NFκB and Wnt/β-catenin transduction signaling leading to increased migration, invasive potential, and cell proliferation as well tumor growth in vivo (Madej et al 2021 ; Wronski et al 2024 ).…”
Section: Introductionmentioning
confidence: 56%
“…Formalin-fixed paraffin-embedded 4 µm melanoma sections were used for both IHC (for RIPK4) and IF (for p65 NFκB subunit), as previously described (Janjetovic et al 2011 ; Madej et al 2021 ). The characteristic of melanoma patients is presented in Supplementary materials Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Melanin pigmentation regulates the expression of multiple genes and plays a critical role in many cellular processes in melanoma cells 10 12 . It can affect the behavior of melanoma cells, their surrounding environment, susceptibility to the therapy, and viability of immune cells 10 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%